PPARA ameliorates sepsis-induced myocardial injury via promoting macrophage M2 polarization by interacting with DUSP1 - Li Cheng; Dezhi Liu; Shanglan Gao (Regenerative Therapy, 2024)
Background: The morbidity and mortality of sepsis are increasing year by year. Statistically, 40–50% of patients with sepsis have concomitant myocardial injury, and its mortality rate is higher than that of patients with sepsis only. Therefore, it is of great significance to elucidate the mechanism of sepsis-induced myocardial injury. Methods and results: Human monocytes (THP-1) were used to induce M0 macrophages, followed by treated with lipopolysaccharide (LPS). Cardiomyocytes (AC16) were co-cultured with the conditioned medium of LPS-induced macrophages to induce injury. Quantitative real-time PCR was employed to detect the mRNA levels of peroxisome proliferator-activated receptor α (PPARA) and dual specificity phosphatase 1 (DUSP1). Protein levels of PPARA, macrophage polarization-related markers, apoptosis-related markers, mitochondria-related proteins, and DUSP1 were analyzed by Western blot. Flow cytometry was used to assess M1/M2 cell rates and apoptosis. Low PPARA expression could serve as a biomarker for patients with sepsis. PPARA overexpression enhanced M2 polarization and suppressed M1 polarization in LPS-induced macrophages, and it could alleviate cardiomyocyte injury in co-cultured system. PPARA bound to the DUSP1 promoter region and facilitated its expression. DUSP1 knockdown reversed the effect of PPARA overexpression on M2 polarization and cardiomyocyte injury. Conclusion: PPARA attenuated cardiomyocyte injury by promoting macrophage M2 polarization through increasing DUSP1 expression, suggesting that PPARA might be a therapy target for sepsis-induced myocardial injury.